A comparative study on the prevalence of musculoskeletal complaints among musicians and non-musicians - Kok Laura M (BMC Musculoskeletal Disorders, 2013)
Abstract Background Research comparing the frequency of musculoskeletal complaints between musicians and non-musicians is scarce. The aim of this study was to compare the prevalence of musculoskeletal complaints between musicians and non-musicians. Methods A cross-sectional study in 3215 students from three music academies (n = 345) and one medical school (n = 2870) in The Netherlands was performed, using an electronic questionnaire. The questionnaire included socio-demographic characteristics, use of music instruments and the occurrence of musculoskeletal complaints in six body regions. Questions were related to musculoskeletal complaints over the last twelve months and at the time of the questionnaire. Chi-square, t-tests and Kruskal-Wallis tests were used for comparison between the two groups. The association between musculoskeletal complaints and possible predictors was analyzed using a logistic and Poisson regression. Results Eighty-seven music academy students and 503 medical students returned the questionnaire, of which respectively eighty-three and 494 were included in the study. Seventy-four music academy students (89.2%) reported one or more musculoskeletal complaints during the last twelve months, compared to 384 (77.9%) medical students (p = 0.019). Moreover 52 music academy students (62.7%) and 211 medical students (42.7%) reported current musculoskeletal complaints (p = 0.001). The Odds ratio (OR) for the development of musculoskeletal complaints during the last twelve months in music academy students versus medical students is 2.33 (95% CI 1.61–3.05, p = 0.022). The OR at the time of the questionnaire is 2.25 (95% CI 1.77–2.73, p = 0.001). The total number of complaints have been modeled by employing a Poisson regression; the results show that non-musicians have on average less complaints than musicians (p = 0.01). The adjusted means are 2.90 (95% CI 2.18–3.63) and 1.83 (95% CI 1.63–2.04) respectively for musicians and non-musicians. Regarding the localization of complaints, music academy students reported more complaints concerning the right hand, wrists, left elbow, shoulders, neck, jaw and mouth in contrast to medical students. Conclusions Musculoskeletal complaints are significantly more common among musicians compared to non-musicians, mainly due to a higher number of upper extremity complaints.